2008
DOI: 10.1080/13557850701803130
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and diabetes among urban Indigenous Australians aged 15–64 years in the DRUID study

Abstract: The relationship between SES and diabetes among Indigenous Australians in this study is consistent with the patterns observed in developed countries, rather than those in some developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
3
39
1
Order By: Relevance
“…Chi et al reported a positive but statistically insignificant association between helicobacter pylori infection and both parental education and income among Aboriginal children in Taiwan (Chi et al 2009). Studies of adult Aboriginal populations in Australia confirm that there are positive gradients with aspects of physical health, including end-stage renal disease, diabetes and cardiovascular disease (Cass et al 2002, Cunningham et al 2008, Cunningham 2010a, 2010b. The results of these studies may not be generalisable to Aboriginal child populations, given the conflicting evidence on the strength of gradients by age (Bartley et al 1997).…”
Section: Positive Gradientsmentioning
confidence: 61%
See 1 more Smart Citation
“…Chi et al reported a positive but statistically insignificant association between helicobacter pylori infection and both parental education and income among Aboriginal children in Taiwan (Chi et al 2009). Studies of adult Aboriginal populations in Australia confirm that there are positive gradients with aspects of physical health, including end-stage renal disease, diabetes and cardiovascular disease (Cass et al 2002, Cunningham et al 2008, Cunningham 2010a, 2010b. The results of these studies may not be generalisable to Aboriginal child populations, given the conflicting evidence on the strength of gradients by age (Bartley et al 1997).…”
Section: Positive Gradientsmentioning
confidence: 61%
“…These factors reflect the way in which society is ordered according to wealth, prestige, power, social standing or one's control over economic resources (Mueller and Parcel 1981). The pattern of association between socio-economic status (SES) and health has almost always Cunningham et al 2008, Oddy et al 2008, Cunningham 2010a, 2010b, although the slope and direction of these gradients typically varies across studies. Mental health, asthma and long-term health conditions appear to be equally prevalent across SES categories (Hunter, 1999, Zubrick et al 2005, Cunningham 2010c, and a single study on birthweight was inconclusive as to whether outcomes varied significantly by an area-based measure of relative disadvantage (Titmuss et al 2008).…”
Section: Socioeconomic Disparities In Physical Health Among Aboriginamentioning
confidence: 99%
“…In an investigation in the Darwin region of Australia, it was reported that the rates of T2DM increased with declining income and socio-economic status in urban Indigenous Australians [41]. Darwin, the capital of the Northern Territory, is the northern-most capital city in Australia, and Indigenous people represent approximately 29% of the Northern Territory population and 10% of the Darwin Region population.…”
Section: Social and Environmental Contributorsmentioning
confidence: 99%
“…Previous reports have shown significant relationships between low SES and increased prevalence of other chronic conditions including diabetes (Cunningham et al 2008;Cunningham 2010a), cardiovascular disease (Cunningham 2010b), and end-stage kidney disease (Cass et al 2001(Cass et al , 2002, but not asthma (Cunningham 2010c).…”
Section: Introductionmentioning
confidence: 99%